(untitled) (Contemporary Journal of Social Science Review, 2025)
The Urdu commentaries on Dhakheerat-ul-Uqba Fi Sharh Al-Mujtaba represent a significant scholarly and research contribution in the field of Islamic sciences. Their most notable feature is their simple and easily comprehensible language, making them accessible not only to scholars but also to general readers. These commentaries simplify complex academic terminologies, ensuring that jurisprudential and Hadith-related points are clearly understood.With a rigorous academic and research-oriented approach, each Hadith and jurisprudential issue is first referenced from its original source, followed by a discussion on its authenticity and reliability. The narrations are analyzed in the light of the opinions of Hadith scholars. Additionally, these commentaries provide an extensive discussion on jurisprudential issues, where different schools of thought are compared, and legal matters are clarified based on principles of Islamic jurisprudence. This makes them beneficial not only for scholars but also for students engaged in modern Islamic research.These commentaries go beyond mere explanation of Hadith; they also include jurisprudential reasoning and fundamental discussions, offering readers comprehensive guidance on various legal issues. Many of them follow a thematic arrangement, making it easier for students and researchers to conduct focused academic studies. Furthermore, they address contemporary scholarly questions, respond to orientalist objections, and discuss modern social and legal challenges, ensuring their relevance in today’s intellectual discourse.Overall, the Urdu commentaries on Dhakheerat-ul-Uqba serve as a valuable resource for students of Islamic sciences, jurists, and researchers. Their academic depth, research standards, jurisprudential reasoning, and guidance on contemporary issues grant them a distinguished status. These commentaries provide a reliable and comprehensive reference for Hadith and jurisprudential studies, preserving traditional interpretations while also contributing to modern scholarly discourse.